Crime thrillers Binge-Watching Behaviour: Association with Personality traits and Impulsivity - Rahul Gupta; Surender kumar; Sanjay gehlot (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
Due to negative consequences associated with binge _watching involving crime thrillers it has become a topic of scientific debate. It has been mediated by biopsychological parameters under the impact of cognitive and affective aspects. To determine the role of Personality traits and Impulsivity in individuals with Crime thrillers Binge-Watching Behaviour. The present cross sectional study has been done through online digital media. The study recruited 160 individuals with administration of information questionnaires to get their demographic details, pattern of crime thrillers series watching, behavioral traits and behavioral impulsivity. Crime thrillers binge-watching was reported by 80 participants (50%) with female predominance (52.9%) and a mean age of 25.2(S.D.2.4) years. Crime thrillers binge watching was found to have 6.31 as the mean maximum number of episodes in a single sitting.However,no significant differences were present with regard to demographic profile of crime thrillers binge watchers as compared to crime thrillers non-binge-watchers (p value >.05).Individuals with crime thrillers binge watching were having higher score involving neuroticism and lower score involving openness and agreeableness in comparison to non binge watching of crime thrillers with statistical significance (p value <.05). Impulsivity (BIS-15), mean (SD) score was found to be higher 30.33(4) in crime thrillers binge_ watching as compared to non _binge watchers. Loss of self Control subscale score was found to be higher in female gender 29.5( mean score) as compared to male gender indicating negative consequences in female gender with more severe loss of control. The study found Impulsivity and personality traits seem to be important pathways for crime thrillers binge watching, neuroticism is higher in binge watching while conscientiousness seems protective factor.